Protein-losing enteropathy in paracoccidioidomycosis identified by scintigraphy: report of three cases - Berni, Aline Dayara de Mendonça (2010)
Paracoccidioidomycosis (PCM) or South American Blastomycosis is a systemic fungal infection caused by a dimorphic fungus, Paracoccidioides brasiliensis. It represents the most important systemic mycosis in South America and with higher prevalence among male inhabitants of the rural area. PCM usually affects the lungs, and rarely the intestines. The authors report three cases of PCM, treated at the University Hospital of Universidade Federal de Mato Grosso do Sul whose scintigraphy with technetium-99 labeled human albumin revead intestinal protein loss.